2017
DOI: 10.1161/circimaging.116.005270
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Cardiac Remodeling in Preadolescents With Fetal Growth Restriction

Abstract: Background— Fetal growth restriction (FGR) affects 5% to 10% of newborns and is associated with increased cardiovascular mortality in adulthood. We evaluated whether prenatal cardiovascular changes previously demonstrated in FGR persist into preadolescence. Methods and Results— A cohort study of 58 FGR (defined as birth weight below 10th centile) and 94 normally grown fetuses identified in utero and followed-up into preadolescence (8–12 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 37 publications
5
84
1
4
Order By: Relevance
“…However, while postnatal cardiac remodeling reverts after treating the cause, cardiac remodeling occurring in utero might persist postnatally even after the trigger has disappeared. Actually, postnatal persistence of fetal cardiac remodeling has been demonstrated in several conditions such as fetal growth restriction, maternal diabetes, exposure to antiretroviral drugs, prematurity, or assisted reproductive technologies [9,10,16,[34][35][36][37][38]. This phenomenon is explained by the fetal programming hypothesis that proposes a prenatal origin for some adult cardiovascular diseases.…”
Section: Resultsmentioning
confidence: 99%
“…However, while postnatal cardiac remodeling reverts after treating the cause, cardiac remodeling occurring in utero might persist postnatally even after the trigger has disappeared. Actually, postnatal persistence of fetal cardiac remodeling has been demonstrated in several conditions such as fetal growth restriction, maternal diabetes, exposure to antiretroviral drugs, prematurity, or assisted reproductive technologies [9,10,16,[34][35][36][37][38]. This phenomenon is explained by the fetal programming hypothesis that proposes a prenatal origin for some adult cardiovascular diseases.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that these early changes are of long-term clinical significance, given that epidemiologic studies have consistently shown an association between IUGR and an increased rate of cardiovascular mortality in adulthood [99]. In line with this, it has been demonstrated that many of the cardiovascular changes that first emerge during fetal life, including cardiac morphological changes, subclinical myocardial dysfunction, arterial remodeling, and impaired endothelial function, persist long-term [94]. DOI: 10.1159/000501906 Preeclampsia Preeclampsia is a common hypertension-related pregnancy complication that is characterized by proteinuria and maternal organ dysfunction (such as renal insufficiency, liver, and placental dysfunction) post 20 weeks' gestation, affecting over 8% of pregnancies worldwide [9,100].…”
Section: Impact Of Pregnancy Complications On Early Cardiac Remodelingmentioning
confidence: 89%
“…IUGR offspring demonstrate early cardiac changes that emerge during fetal life and persist into neonatal life, including a relatively hypertrophied ventricular septum, LV dilatation, decreased myocardial reserve, a more globular cardiac morphology, and abnormal early postnatal hemodynamic adaptations [8,[93][94][95]. Furthermore, IUGR neonates exhibit an increase in left myocardial performance index (a marker of ventricular dysfunction), an inability to increase LV stroke volume, as well as reduced heart rate in the first week of postnatal life when compared with appropriate-for-gestational-age controls [8,96].…”
Section: Impact Of Pregnancy Complications On Early Cardiac Remodelingmentioning
confidence: 99%
“…It affects about 5-10% of all pregnancies, and is one of the main causes of perinatal morbidity and mortality worldwide 3 . Apart from perinatal complications, individuals born small present long-term consequences, with an increased risk for cardiovascular and metabolic disease in adulthood [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%